Negative electrode sheet, method for manufacturing the same, solid-state battery, battery pack, and terminal
Patent Information
- Application Number
- CN202610970712.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本申请实施例的目的是提供一种负极极片及其制备方法、固态电池、电池包及终端,至少解决现有硫化物固态电池的负极极片容易因负极材料膨胀以及硫化物固态电解质与负极材料之间的接触反应,导致倍率性能以及循环寿命快速衰减的问题
[0017]在本申请实施例中,负极极片包括负极集流体以及设置于负极集流体至少一面上的负极活性材料层,负极活性材料层包括第一硫化物固态电解质、负极活性颗粒和导电剂,负极活性颗粒包括内核以及设置于内核表面的包覆层,内核包括负极活性材料,包覆层包括无机锂盐、烷基碳酸锂以及聚碳酸酯;其中,因为无机锂盐、烷基碳酸锂以及聚碳酸酯具有较低的表面能,能够优先润湿并均匀包覆在负极活性材料表面,形成兼具无机物硬度与有机物柔韧性的包覆层,可以将负极活性材料与硫化物电解质有效隔离,从而抑制硫化物电解质的还原分解,使得界面阻抗显著降低,界面稳定性大幅提高;同时,包覆层具有良好的柔韧性和机械强度,能够有效缓冲硅负极在循环过程中的体积膨胀,保持极片结构的完整性,避免因体积效应导致的接触失效,使得电池的循环寿命得到极大提升;另外,包覆层提供了高效的锂离子传输通道,改善了界面动力学,使得电池在较高倍率下仍能保持较高的容量发挥。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This application belongs to the field of battery technology, specifically relating to a negative electrode sheet and its preparation method, a solid-state battery, a battery pack, and a terminal. Background Technology
[0002] In recent years, all-solid-state batteries designed using sulfide solid electrolytes with high lithium-ion conductivity have attracted widespread attention from researchers. The negative electrode of a sulfide solid-state battery is typically made of a negative electrode active material (such as silicon-based materials, graphite, etc.), a sulfide solid electrolyte, a conductive agent, a binder, etc.
[0003] However, high-capacity silicon and other anode materials undergo huge volume changes (>300%) during charge and discharge. Furthermore, the interface between the anode material and the sulfide electrolyte is a solid-solid "point contact" with weak bonding. Contact failure is very likely to occur when the volume expands, leading to rapid capacity decay. At the same time, sulfide solid electrolytes (such as LGPS, LPSCl, etc.) have a narrow electrochemical window and are sensitive to reduction potential. When they come into direct contact with low-potential anode materials, severe reduction decomposition reactions occur, generating high-resistivity byproducts (such as Li2S, P2S5, etc.) at the interface. This significantly increases the interface impedance and deteriorates the rate performance and cycle life of the battery. Summary of the Invention
[0004] The purpose of this application is to provide a negative electrode sheet and its preparation method, a solid-state battery, a battery pack, and a terminal, at least to solve the problem that the negative electrode sheet of existing sulfide solid-state batteries is prone to rapid degradation of rate performance and cycle life due to the expansion of the negative electrode material and the contact reaction between the sulfide solid electrolyte and the negative electrode material.
[0005] In a first aspect, embodiments of this application provide a negative electrode sheet, the negative electrode sheet comprising a negative current collector and a negative active material layer disposed on at least one side of the negative current collector, the negative active material layer comprising a first sulfide solid electrolyte, negative active particles and a conductive agent, the negative active particles comprising a core and a coating layer disposed on the surface of the core, the core comprising a negative active material, and the coating layer comprising an inorganic lithium salt, alkyl lithium carbonate and polycarbonate.
[0006] Optionally, in the negative electrode sheet, the inorganic lithium salt includes at least one of Li2CO3, LiF, Li2S, and Li3P.
[0007] Optionally, in the negative electrode sheet, the thickness of the coating layer is 2~20 nm.
[0008] Optionally, in the negative electrode, the first sulfide solid electrolyte includes Li6PS5Cl and Li 10 GeP2S12 Li7P3S 11 At least one of Li3PS4; and / or, The negative electrode active material includes at least one of pure silicon, silicon carbide, and graphite; and / or, The conductive agent includes at least one of carbon black, acetylene black, carbon nanotubes, graphene, and vapor-grown carbon fibers.
[0009] Optionally, in the negative electrode sheet, the particle size of the first sulfide solid electrolyte is 0.1~2 μm.
[0010] Optionally, in the negative electrode sheet, the negative electrode active material layer further includes a binder, the binder being selected from at least one of styrene-butadiene rubber, polyvinylidene fluoride, polyacrylic acid, hydrogenated nitrile rubber, and hydrogenated styrene-butadiene block copolymer.
[0011] Secondly, embodiments of this application provide a method for preparing the above-mentioned negative electrode sheet, comprising: The negative electrode active material, the first sulfide solid electrolyte, the conductive agent and the five-membered cyclic carbonate are added to the solvent and homogenized to allow the five-membered cyclic carbonate to react with part of the first sulfide solid electrolyte and form a coating layer on the surface of the negative electrode active material to form a negative electrode slurry. The negative electrode slurry is scraped onto the surface of the negative electrode current collector to obtain the negative electrode sheet.
[0012] Optionally, in the preparation method, the five-membered cyclic carbonate includes at least one of vinylene carbonate, fluoroethylene carbonate, ethylene carbonate, ethylene ethylene carbonate, and difluoroethylene carbonate.
[0013] Optionally, in the preparation method, the mass ratio of the negative electrode active material, the first sulfide solid electrolyte, the conductive agent, and the five-membered cyclic carbonate is 100:(1~50):(0.5~10):(0.1~3); and / or, The homogenization temperature is controlled at 20~60℃, the time is 0.5~4 hours, and the stirring speed is 500~2000 rpm; and / or, The homogenization process includes mechanical stirring or ball milling under inert atmosphere or dry room conditions with a dew point ≤ -30°C.
[0014] Thirdly, embodiments of this application provide a solid-state battery, including the aforementioned negative electrode, positive electrode, and solid electrolyte membrane, wherein the solid electrolyte membrane is disposed between the positive electrode and the negative electrode.
[0015] Fourthly, embodiments of this application provide a battery pack including the solid-state battery as described above.
[0016] Fifthly, embodiments of this application provide a terminal including the aforementioned battery pack, wherein the battery pack serves as the power supply for the terminal.
[0017] In this embodiment, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one side of the negative current collector. The negative active material layer includes a first sulfide solid electrolyte, negative active particles, and a conductive agent. The negative active particles include a core and a coating layer disposed on the surface of the core. The core includes a negative active material, and the coating layer includes an inorganic lithium salt, alkyl lithium carbonate, and polycarbonate. Because the inorganic lithium salt, alkyl lithium carbonate, and polycarbonate have low surface energy, they can preferentially wet and uniformly coat the surface of the negative active material, forming a structure that combines the hardness of inorganic materials with the flexibility of organic materials. The coating layer effectively isolates the negative electrode active material from the sulfide electrolyte, thereby inhibiting the reduction and decomposition of the sulfide electrolyte, significantly reducing interfacial impedance and greatly improving interfacial stability. At the same time, the coating layer has good flexibility and mechanical strength, which can effectively buffer the volume expansion of the silicon negative electrode during cycling, maintain the integrity of the electrode structure, and avoid contact failure caused by volume effect, thus greatly improving the cycle life of the battery. In addition, the coating layer provides a highly efficient lithium-ion transport channel, improves interfacial dynamics, and enables the battery to maintain a high capacity even at high rates. Detailed Implementation
[0018] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to specific embodiments.
[0019] The terms "first" and "second" in the specification and claims of this application may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise stated, "multiple" means two or more. Furthermore, "and / or" in the specification and claims indicates at least one of the connected objects, and the character " / " generally indicates that the preceding and following objects are in an "or" relationship.
[0020] In recent years, all-solid-state batteries designed using sulfide solid-state electrolytes with high lithium-ion conductivity have attracted widespread attention from researchers. The negative electrode of sulfide all-solid-state batteries is mainly prepared using a wet process. This method typically involves mixing the negative electrode active material (such as silicon-based materials, graphite, etc.), sulfide solid-state electrolyte, conductive agent, binder, and solvent to form a slurry, which is then coated and dried to obtain the negative electrode sheet.
[0021] However, existing processes have the following prominent problems: First, high-capacity silicon-based anode materials exhibit significant volume changes (>300%) during charge and discharge. Although solid-state electrolytes in all-solid-state batteries possess some mechanical inhibition capabilities, in traditional methods, the anode material and sulfide electrolyte are merely physically mixed, resulting in a weak solid-solid "point contact" interface. This weak bonding makes them highly susceptible to contact failure during volume expansion, leading to rapid capacity decay. Second, sulfide solid electrolytes (such as LGPS and LPSCl) have narrow electrochemical windows and are sensitive to reduction potentials. When in direct contact with low-potential anode materials, severe reduction decomposition reactions occur, generating high-resistivity byproducts (such as Li2S and P2S5) at the interface. This significantly increases interfacial impedance, deteriorating the battery's rate performance and cycle life.
[0022] In related technologies, a strategy of pre-coating the negative electrode material is adopted, such as coating the silicon particle surface with a carbon layer, oxide layer (such as Al2O3), or ion conductor layer through atomic layer deposition (ALD), chemical vapor deposition (CVD), or complex liquid phase methods. However, these methods are complex, costly, and difficult to achieve uniform and dense coating, which is not conducive to large-scale industrial production.
[0023] To address the aforementioned issues, embodiments of this application provide a negative electrode sheet. The negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one side of the negative current collector. The negative active material layer includes a first sulfide solid electrolyte, negative active particles, and a conductive agent. The negative active particles include a core and a coating layer disposed on the surface of the core. The core includes a negative active material, and the coating layer includes an inorganic lithium salt, alkyl lithium carbonate, and polycarbonate.
[0024] In this embodiment, by adding a five-membered cyclic carbonate during the homogenization process to chemically react with the sulfide solid electrolyte, reaction products such as inorganic lithium salts, alkyl lithium carbonates, and polycarbonates are formed in a liquid slurry environment. Because inorganic lithium salts, alkyl lithium carbonates, and polycarbonates have low surface energy, they can preferentially wet and uniformly coat the surface of the negative electrode active material, achieving "in-situ" formation and uniform coating on the surface of the negative electrode material. This forms a coating layer that combines the hardness of inorganic materials with the flexibility of organic materials, effectively isolating the negative electrode active material from the sulfide solid electrolyte and thus inhibiting the reduction of the sulfide solid electrolyte. The coating layer decomposes and avoids the formation of a high-resistivity interface layer, reducing interface impedance and improving initial coulombic efficiency and cycle stability. Simultaneously, the coating layer possesses good flexibility and mechanical strength, allowing it to adhere tightly to the surface of the negative electrode active material without easily detaching. This effectively buffers the volume expansion of the negative electrode during cycling, preventing interface contact failure and electrode pulverization caused by volume effects, maintaining structural integrity during long cycles, and significantly improving the battery's cycle life. Furthermore, the coating layer provides efficient lithium-ion transport channels, improving interface dynamics and enabling the battery to maintain high capacity even at higher rates.
[0025] Therefore, in this embodiment, a coating layer with high ionic conductivity, high mechanical strength, and high electrochemical stability is constructed on the surface of the negative electrode active material. This layer can effectively buffer volume changes, suppress side reactions, and provide a high-speed transport channel for lithium ions. It can effectively improve the problem that the negative electrode sheet of existing sulfide solid-state batteries is prone to rapid decay of rate performance and cycle life due to the expansion of the negative electrode material and the contact reaction between the sulfide solid electrolyte and the negative electrode material.
[0026] Experiments show that the solid-state battery prepared using the embodiments of this application can retain more than 80% of its capacity after 500 cycles at 0.5C rate, and its high electrochemical stability is reflected in the 20% increase in capacity retention after 500 cycles.
[0027] Among them, the surface energy of the above-mentioned inorganic lithium salt is less than or equal to 450 mN / m, the surface energy of alkyl lithium carbonate is 25~30 mN / m, and the surface energy of polycarbonate is 20~25 mN / m.
[0028] Optionally, in one embodiment, the composition of the coating layer can be controlled by adjusting the type and proportion of the five-membered cyclic carbonates to regulate the composition of the reaction products. The five-membered cyclic carbonates include at least one of vinylene carbonate, fluoroethylene carbonate, ethylene carbonate, ethylene ethylene carbonate, and difluoroethylene carbonate.
[0029] Optionally, in one embodiment, the negative electrode active material includes at least one of pure silicon, silicon carbide, and graphite, which can improve the volume expansion during cycling through the above-mentioned coating layer, thereby giving full play to its high capacity advantage and effectively improving energy density.
[0030] Optionally, in one embodiment, the particle size of pure silicon is 0.1~10 μm, the mass fraction of silicon in the silicon-carbon composite material is 1%~70%, and the particle size of graphite is 1~10 μm.
[0031] Optionally, in one embodiment, the inorganic lithium salt includes at least one of Li2CO3, LiF, Li2S, and Li3P. These substances not only have high hardness and can improve lithium-ion transport efficiency, but are also suitable for in-situ formation of sulfide solid electrolytes through ring-opening polymerization or decomposition reactions of five-membered cyclic carbonates.
[0032] Optionally, in one embodiment, the thickness of the coating layer is 2-20 nm, which can effectively isolate the electrolyte and negative electrode active material to suppress side reactions and volume expansion, while also ensuring lithium-ion conduction and avoiding affecting the battery rate performance. In some embodiments, the thickness of the coating layer can be one or any two of the following: 2 nm, 3 nm, 5 nm, 8 nm, 10 nm, 15 nm, and 20 nm.
[0033] Optionally, in one embodiment, cross-sectional observation and thickness measurement can be performed using a scanning electron microscope or a transmission electron microscope, and the elemental composition of the coating layer can be verified by EDS line scanning or EELS surface distribution analysis to detect the presence of the coating layer and measure its thickness.
[0034] Optionally, in one embodiment, the first sulfide solid electrolyte includes Li6PS5Cl, Li 10 GeP2S 12 Li7P3S 11 At least one of Li3PS4 can be effectively dispersed within the negative electrode slurry to construct a continuous ionic conductive network, and its surface contains Lewis acid sites (such as P...). 5+ (S vacancy) is suitable for interacting with double bonds and carbonate groups in five-membered cyclic carbonates, initiating ring-opening polymerization or decomposition reactions, thereby forming inorganic lithium salts, alkyl lithium carbonates and polycarbonates as components of the coating layer in situ.
[0035] Optionally, in one embodiment, the particle size of the first sulfide solid electrolyte is 0.1~2 μm, for example, a range of one or any two of 0.1 μm, 0.2 μm, 0.5 μm, 0.8 μm, 1.0 μm, 1.5 μm, 2 μm, suitable for forming effective solid-solid contact with the negative electrode active particles to form a complete conductive network.
[0036] Optionally, in one embodiment, the conductive agent is dispersed between the first sulfide solid electrolyte, thereby achieving a structure similar to reinforced concrete, with an ion-conducting network as the main body and an electronic-conducting network interspersed therein, resulting in better rate performance and better fast charging and discharging performance.
[0037] Optionally, in one embodiment, the conductive agent includes at least two of carbon black, acetylene black, carbon nanotubes, graphene, and vapor-grown carbon fibers.
[0038] In this specific embodiment, carbon black is granular, graphene is sheet-like, carbon nanotubes are strip-like, and carbon nanofibers are linear. Using at least two of the aforementioned conductive agents can construct a three-dimensional interpenetrating conductive network, ensuring the continuity of the electronic conduction path and thus improving the battery's fast-charging performance. Specifically, the carbon nanofibers can be vapor-grown carbon fibers (VGCF).
[0039] Optionally, in one embodiment, the negative electrode active material layer further includes an adhesive selected from at least one of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), hydrogenated nitrile butadiene rubber (HNBR), and hydrogenated styrene-butadiene block copolymer (SEBS). These molecular structures contain polar groups or flexible segments, which can bond to the surface of the adherend through van der Waals forces, hydrogen bonds, or mechanical intercalation. They are not easily decomposed or reacted in conventional use environments, exhibiting good chemical stability. Furthermore, they can form a uniform slurry through dissolution or emulsion dispersion, resulting in a continuous film after coating, thereby encapsulating and connecting the dispersed particles into a whole, demonstrating good film-forming properties and continuity.
[0040] This application also provides a solid-state battery, including the above-mentioned negative electrode, positive electrode, and solid electrolyte membrane disposed between the positive electrode and the negative electrode.
[0041] Optionally, in one embodiment, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector, wherein the positive active material layer includes a positive active material and a second sulfide solid electrolyte.
[0042] In this embodiment, the solid-state battery further includes a positive electrode that matches the aforementioned negative electrode. The positive electrode includes a positive current collector serving as mechanical support and an electronic conduction path, and a positive active material layer coated on one or both sides of the positive current collector. The positive and negative electrodes are separated by a solid electrolyte membrane to prevent internal short circuits while allowing lithium-ion migration.
[0043] Optionally, in one embodiment, the positive electrode active material comprises a lithium-ion transition metal oxide. This lithium-ion transition metal oxide includes at least one of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, and nickel-cobalt-aluminum ternary materials. These materials are capable of accepting and storing lithium ions from the negative electrode during charging, and releasing the lithium ions back to the negative electrode during discharging. Among these, nickel-cobalt-manganese ternary materials include, for example, LiNi... 0.8 Co 0.1 Mn 0.1 O2, or NCM811 for short, is a high-nickel cathode material that can provide high reversible capacity and energy density. The second electrolyte can construct a continuous and efficient ion transport channel in the positive electrode active material layer, ensuring that lithium ions migrating from the electrolyte layer can quickly and uniformly penetrate to the surface of the positive electrode active material particles and participate in the electrochemical reaction.
[0044] Optionally, in one embodiment, the positive electrode further includes a conductive agent, which may include at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, hard carbon, carbon fiber, and carbon microspheres.
[0045] Optionally, in one embodiment, the positive electrode active material layer further includes a binder, wherein the binder is selected from one or more of styrene-butadiene rubber, polyvinylidene fluoride, polyacrylic acid, hydrogenated nitrile rubber, hydrogenated styrene-butadiene block copolymer, carboxylated styrene-butadiene latex, polyvinyl alcohol, sodium carboxymethyl cellulose and polytetrafluoroethylene.
[0046] In some embodiments, the positive electrode sheet is prepared as follows: the components used to prepare the positive electrode sheet, such as the positive active material including the above-mentioned positive electrode material, the second sulfide solid electrolyte, the binder and the conductive agent, are dispersed in a solvent such as N-methylpyrrolidone to form a positive electrode slurry; the positive electrode slurry is coated on a positive electrode current collector such as aluminum foil; after drying, rolling, die cutting and other processes, the positive electrode sheet can be obtained.
[0047] In some embodiments, the solid electrolyte membrane includes a third sulfide solid electrolyte, which is filled between the positive electrode and the negative electrode.
[0048] In this embodiment, the solid-state battery system of the present invention further includes a third sulfide solid electrolyte, with positive and negative electrodes spaced apart, and the third sulfide solid electrolyte filling the gap between the positive and negative electrodes, forming an ion conduction body connecting the two electrodes.
[0049] In this embodiment, the first sulfide solid electrolyte is distributed inside the negative electrode active material layer, forming an ion transport channel in the negative electrode active material layer; the second sulfide solid electrolyte is distributed inside the positive electrode active material layer, forming an ion transport channel in the positive electrode active material layer; and the third sulfide solid electrolyte serves as an ion transport bridge connecting the positive and negative electrodes. The three work together to ensure that lithium ions can smoothly and quickly complete migration and cycling throughout the battery.
[0050] In some embodiments, the second sulfide solid electrolyte and the third sulfide solid electrolyte can be independently derived from Li6PS5Cl, Li 10 GeP2S 12 Li7P3S 11 It can be selected from at least one of Li3PS4, and its preparation method is relatively simple. It can be prepared by simple solid-phase reaction or liquid-phase method, and has a wide electrochemical stability window and is relatively stable to lithium metal anode.
[0051] It should be noted that the solid-state battery disclosed in this application is a basic building block of a battery system, and can be used independently as a complete battery product. Each solid-state battery includes key components such as a positive electrode, a negative electrode, and an electrolyte, and stores and releases energy through internal electrochemical reactions. In practical applications, depending on different usage scenarios and performance requirements, solid-state batteries can adopt various packaging forms such as cylindrical, prismatic, or pouch cells, and their capacity and size can also be adjusted and optimized accordingly. This application also discloses a battery pack. In some embodiments, the battery pack is formed by connecting the solid-state batteries of this application in series and parallel. The number of solid-state batteries in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module. It should be noted that the solid-state batteries included in the battery module disclosed in this application have the same structure as the solid-state batteries in the above embodiments, and their beneficial effects are also similar, so they will not be described again here.
[0052] This application also discloses a battery pack. In some embodiments, the battery pack includes the battery pack described above, as well as supporting key components such as a battery management system, a thermal management system, and safety protection devices. The battery pack may contain one or more battery packs, and the specific number can be selected by those skilled in the art based on the application and capacity of the battery pack.
[0053] This application also discloses a terminal, which includes a solid-state battery, battery pack, or battery group as described in the embodiments of this application. The solid-state battery, battery module, or battery group is electrically connected to the electrical device and can provide power to the terminal.
[0054] Specifically, the aforementioned electrical equipment can be, but is not limited to, vehicles, electric vehicles, mobile phones, tablets, laptops, electric toys, robots, ships, spacecraft, etc. Among them, electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc., and spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.
[0055] It should be noted that, in the embodiments of this application, the types of vehicles include, but are not limited to, pure electric vehicles and hybrid vehicles.
[0056] The above-described solid-state battery, battery pack, and terminal embodiments all include the aforementioned negative electrode sheet and achieve the same technical effect. To avoid repetition, they will not be described again here. For relevant details, please refer to the description of the negative electrode sheet embodiments.
[0057] This application also discloses a method for preparing a negative electrode sheet, including steps 101 to 102: Step 101: Add the negative electrode active material, the first sulfide solid electrolyte, the conductive agent and the five-membered cyclic carbonate to the solvent, homogenize the mixture so that the five-membered cyclic carbonate reacts with part of the first sulfide solid electrolyte and forms a coating layer on the surface of the negative electrode active material to form a negative electrode slurry. Step 102: Apply the negative electrode slurry to the surface of the negative electrode current collector to obtain the negative electrode sheet.
[0058] In this embodiment, a five-membered cyclic carbonate is directly introduced into the homogenized slurry system. The chemical reaction between the five-membered cyclic carbonate and the sulfide solid electrolyte forms reaction products such as inorganic lithium salts, alkyl lithium carbonates, and polycarbonates in a liquid-phase slurry environment. Because inorganic lithium salts, alkyl lithium carbonates, and polycarbonates have low surface energy, they can preferentially wet and uniformly coat the surface of the negative electrode active material, achieving "in-situ" formation and uniform coating on the negative electrode material surface. This forms a coating layer that combines the hardness of inorganic materials with the flexibility of organic materials, effectively isolating the negative electrode active material from the sulfide solid electrolyte, thereby suppressing the sulfide solid electrolyte. The reduction and decomposition of the electrolyte avoids the formation of a high-resistivity interface layer, reduces interface impedance, and improves initial coulombic efficiency and cycle stability. Simultaneously, the coating layer possesses excellent flexibility and mechanical strength, allowing it to adhere tightly to the surface of the negative electrode active material without easily detaching. This effectively buffers the volume expansion of the negative electrode during cycling, preventing interfacial contact failure and electrode pulverization caused by volume effects, maintaining structural integrity during long cycles, and significantly improving the battery's cycle life. Furthermore, the coating layer provides efficient lithium-ion transport channels, improving interfacial dynamics, enabling the battery to maintain high capacity even at higher rates.
[0059] The preparation method provided in this application uses a coating layer generated by liquid-phase reaction, which can achieve uniform coating of the entire surface of the negative electrode material particles without dead corners. This not only results in a tighter interface bond, but also avoids the use of complex pre-coating equipment (such as ALD, CVD) or additional processes, enabling integrated, low-cost, and large-scale preparation of negative electrode sheets. It is applicable to various negative electrode material systems such as pure silicon, silicon carbide, and graphite.
[0060] Optionally, in one embodiment, the aforementioned five-membered cyclic carbonate includes at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), ethylene carbonate (EC), ethylene ethylene carbonate (VEC), and difluoroethylene carbonate (DFEC), capable of reacting with Lewis acid sites (such as P) on the surface of the sulfide solid electrolyte. 5+The interaction of ions (S vacancy) triggers ring-opening polymerization or decomposition reactions, generating inorganic lithium salts, alkyl lithium carbonates, and polycarbonates as reaction products. The inorganic lithium salts include Li2CO3, Li2S, and Li3P. In the case of fluoroethylene carbonate, LiF and polyfluoroethylene carbonate can be further generated, synergistically forming a mixture that combines the hardness of inorganic materials with the flexibility of organic materials.
[0061] Optionally, in one embodiment, the mass ratio of the negative electrode active material, the first sulfide solid electrolyte, the conductive agent, and the five-membered cyclic carbonate is 100:(1~50):(0.5~10):(0.1~3), for example, it can be one or any two of the following: 100:1:0.5:3, 100:25:5:2, 100:50:10:1. This can effectively balance the energy density, ion conduction performance, and electron conduction performance of the negative electrode active material layer, and fully react to form a coating layer that can reduce side reactions.
[0062] Optionally, the solvent should be used in appropriate amounts to control the solid content of the slurry to be 30% to 60% to suit coating. The solvent is a non-polar or weakly polar organic solvent, such as at least one of toluene, xylene, anisole, hexane, n-heptane, butyl butyrate, isobutyl isobutyrate, and anisole.
[0063] Optionally, in one embodiment, the homogenization temperature is controlled at 20~60℃, the time is 0.5~4 hours, and the stirring speed is 500~2000 rpm, so that during the homogenization process, the five-membered cyclic carbonate and the sulfide solid electrolyte undergo an in-situ chemical reaction to generate reaction products such as inorganic lithium salt, alkyl lithium carbonate and polycarbonate, thereby forming a coating layer with a thickness of 2~20 nm on the negative electrode active material film.
[0064] Optionally, in one embodiment, the homogenization process includes mechanical stirring or ball milling under inert atmosphere or dry room conditions with a dew point ≤ -30°C.
[0065] In this embodiment, mechanical stirring or ball milling under inert atmosphere or dry room conditions with a dew point ≤ -30°C can not only effectively promote the in-situ chemical reaction between the five-membered cyclic carbonate and the sulfide solid electrolyte, but also reduce the occurrence of side reactions, thereby improving the overall performance of the formed coating layer.
[0066] Optionally, in one embodiment, the negative electrode slurry further includes a binder selected from at least one of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), hydrogenated nitrile butadiene rubber (HNBR), and hydrogenated styrene-butadiene block copolymer (SEBS). The mass ratio of the binder to the negative electrode active material is 0.5~15:100 to effectively and uniformly bond the negative electrode active particles, the first sulfide solid electrolyte, and the conductive agent.
[0067] Optionally, in one embodiment, in step 102 above, the uniform slurry obtained in step 101 is coated on the negative electrode current collector. The negative electrode current collector can be copper foil, nickel foil, stainless steel foil or carbon-coated copper foil, with a thickness of 6~20 μm, which can take into account energy density, areal capacity and dynamic performance.
[0068] Optionally, in one embodiment, the coating method may be scraping, slot extrusion or transfer coating, and the coating thickness is controlled to be 30~150 μm after drying.
[0069] Optionally, in one embodiment, the coated material can be dried under vacuum or an inert atmosphere at a temperature of 40-100°C for 6-24 hours to completely remove the solvent and obtain a sulfide all-solid-state battery negative electrode sheet.
[0070] Optionally, in one embodiment, the dried negative electrode sheet in step 102 can be subjected to hot pressing or cold pressing at a pressure of 100~500 MPa to improve the electrode density and interface contact.
[0071] In this embodiment, the entire preparation process is carried out at a temperature of <200 °C, which can avoid excessive oxidation of silicon or decomposition of sulfides and is compatible with Cu foil and aluminum-plastic film.
[0072] To make the inventive objectives, technical solutions, and beneficial effects of this invention clearer, the invention is further described below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.
[0073] The present invention will be described in detail below through embodiments.
[0074] Test method: (1) Ratio performance test The battery cell was charged and discharged at 0.2C for 3 cycles at 2.5~4.25V to determine its capacity. Then, based on the determined capacity, charge and discharge tests were conducted at 0.5C, 1C, and 2C rates at 2.5~4.25V, and the discharge capacity retention rate was recorded.
[0075] (2) Cyclic performance test The battery cells were charged and discharged at 25°C at a rate of 0.5C within a range of 2.5 to 4.25V. The discharge specific capacity of the battery in the first cycle and the discharge specific capacity after 500 cycles were recorded. The capacity retention rate after 500 cycles was calculated as: discharge specific capacity of 500 cycles / discharge specific capacity in the first cycle * 100%.
[0076] (3) Electrode expansion rate test: The cell was charged and discharged at 25°C at a rate of 0.5C within a range of 2.5~4.25V for 100 cycles. After disassembling the battery, the thickness change of the negative electrode was measured using a micrometer. Example 1 (1) Preparation of negative electrode sheet S1. Weigh out the following materials in a mass ratio of 100:20:3:2:0.5: silicon powder (micron-sized negative electrode active material), Li6PS5Cl (sulfide solid electrolyte), SEBS (binder), VGCF (conductive carbon), and additives. Add a certain amount of butyl butyrate. Homogenize the mixture under an argon atmosphere with a water and oxygen content of <1 ppm. This allows the additives to react with some of the sulfide solid electrolyte and form a 10 nm thick coating layer on the surface of the negative electrode active material, thus obtaining the negative electrode slurry. The additive is VC, the sulfide solid electrolyte has a particle size of 1 μm, the homogenization temperature is controlled at 40℃, the time is 2 hours, and the stirring speed is 1000 rpm. S2. The negative electrode slurry is coated on copper foil, and after drying and rolling, a negative electrode sheet is obtained.
[0077] (2) Preparation of positive electrode sheet Weigh out the positive electrode active material NCM811, sulfide solid electrolyte Li6PS5Cl, binder SEBS and conductive carbon VGCF in a mass ratio of 100:20:3:2, add a certain amount of butyl butyrate and mix evenly, coat it on aluminum foil, and obtain the positive electrode sheet after drying and rolling.
[0078] (3) Preparation of solid electrolyte membrane The sulfide solid electrolyte Li6PS5Cl and the binder SEBS were mixed in a 100:4 mass ratio in butyl butyrate solvent to obtain a uniform electrolyte slurry. The electrolyte slurry was coated onto a PET substrate by a scraping method, and then dried in a vacuum environment to completely remove the solvent, forming a self-supporting pre-film as a solid electrolyte membrane.
[0079] (4) Preparation of solid-state batteries All-solid-state batteries are obtained by stacking, encapsulating, and isostatic pressing the negative electrode, solid electrolyte membrane, and positive electrode in that order.
[0080] Example 2 The only difference from Example 1 is that the additive in step S1 is changed to fluoroethylene carbonate (FEC).
[0081] Example 3 The only difference from Example 1 is that in step S1, the additive is adjusted to be a mixture of VC and FEC in a mass ratio of 1:1.
[0082] Examples 4-7 The only difference from Example 1 is that the amount of additive added in step S1 is adjusted to 0.1 parts, 1 part, 3 parts, and 5 parts respectively.
[0083] Examples 8-9 The only difference from Example 1 is that in step S1, the negative electrode active materials are adjusted to be a silicon-carbon composite material with a silicon mass fraction of 50% and a graphite negative electrode material.
[0084] Examples 10-11 The only difference from Example 1 is that the particle size of the sulfide solid electrolyte is adjusted to 0.1 μm and 2 μm in step S1.
[0085] Example 12 The only difference from Example 1 is that in step S1, the sulfide solid electrolyte is adjusted to Li. 10 GeP2S 12 .
[0086] Comparative Example 1 The only difference from Example 1 is that no additives are added in step S1.
[0087] Comparative Example 2 The only difference from Comparative Example 1 is that in step S1, a layer of amorphous carbon with a thickness of 5 nm is pre-coated on the surface of the silicon anode using CVD.
[0088] The structural differences of the negative electrode active particles in the negative electrode sheets prepared in each embodiment and comparative example are shown in Table 1.
[0089] Table 1
[0090] The negative electrode sheets prepared in each embodiment and comparative example were subjected to electrode expansion rate testing, and the battery was subjected to rate performance testing and cycle performance testing. The test data are shown in Table 2.
[0091] Table 2
[0092] In summary, in this embodiment, by forming a coating layer composed of inorganic lithium salt, alkyl lithium carbonate, and polycarbonate on the surface of the negative electrode active material, a coating layer combining the hardness of inorganic materials and the flexibility of organic materials is formed. This effectively isolates the negative electrode active material from the sulfide electrolyte, thereby inhibiting the reduction and decomposition of the sulfide electrolyte, significantly reducing interfacial impedance, and greatly improving interfacial stability. At the same time, the coating layer has good flexibility and mechanical strength, which can effectively buffer the volume expansion of the silicon negative electrode during cycling, maintain the integrity of the electrode structure, and avoid contact failure caused by volume effects, thus greatly improving the cycle life of the battery. In addition, the coating layer provides a highly efficient lithium-ion transport channel, improves interfacial dynamics, and enables the battery to maintain a high capacity even at high rates.
[0093] Although preferred embodiments of the present invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of the present invention.
[0094] The foregoing has provided a detailed description of the negative electrode sheet and its preparation method, solid-state battery, battery pack, and vehicle provided by the present invention. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A negative electrode sheet, characterized in that, The negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one side of the negative current collector. The negative active material layer includes a first sulfide solid electrolyte, negative active particles, and a conductive agent. The negative active particles include a core and a coating layer disposed on the surface of the core. The core includes a negative active material, and the coating layer includes an inorganic lithium salt, an alkyl lithium carbonate, and a polycarbonate.
2. The negative electrode sheet according to claim 1, characterized in that, The inorganic lithium salt includes at least one of Li2CO3, LiF, Li2S, and Li3P.
3. The negative electrode sheet according to any one of claims 1 to 2, characterized in that, The thickness of the coating layer is 2~20 nm.
4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that, The first sulfide solid electrolyte includes Li6PS5Cl and Li 10 GeP2S 12 Li7P3S 11 At least one of Li3PS4; and / or, The negative electrode active material includes at least one of pure silicon, silicon carbide, and graphite; and / or, The conductive agent includes at least one of carbon black, acetylene black, carbon nanotubes, graphene, and vapor-grown carbon fibers.
5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that, The particle size of the first sulfide solid electrolyte is 0.1~2 μm.
6. The negative electrode sheet according to any one of claims 1 to 5, characterized in that, The negative electrode active material layer further includes an adhesive, which is selected from at least one of styrene-butadiene rubber, polyvinylidene fluoride, polyacrylic acid, hydrogenated nitrile rubber, and hydrogenated styrene-butadiene block copolymer.
7. A method for preparing a negative electrode sheet as described in any one of claims 1 to 6, characterized in that, include: The negative electrode active material, the first sulfide solid electrolyte, the conductive agent and the five-membered cyclic carbonate are added to the solvent and homogenized to allow the five-membered cyclic carbonate to react with part of the first sulfide solid electrolyte and form a coating layer on the surface of the negative electrode active material to form a negative electrode slurry. The negative electrode slurry is scraped onto the surface of the negative electrode current collector to obtain the negative electrode sheet.
8. The preparation method according to claim 7, characterized in that, The five-membered cyclic carbonate includes at least one of vinylene carbonate, fluoroethylene carbonate, ethylene carbonate, and difluoroethylene carbonate.
9. The preparation method according to claim 7 or 8, characterized in that, The mass ratio of the negative electrode active material, the first sulfide solid electrolyte, the conductive agent, and the five-membered cyclic carbonate is 100:(1~50):(0.5~10):(0.1~3); and / or, The homogenization temperature is controlled at 20~60℃, the time is 0.5~4 hours, and the stirring speed is 500~2000 rpm; and / or, The homogenization process includes mechanical stirring or ball milling under inert atmosphere or dry room conditions with a dew point ≤ -30°C.
10. A solid-state battery, characterized in that, It includes the negative electrode, positive electrode, and solid electrolyte membrane as described in claims 1 to 6, wherein the solid electrolyte membrane is disposed between the positive electrode and the negative electrode.
11. A battery pack, characterized in that, Including the solid-state battery as described in claim 10.
12. A terminal, characterized in that, Includes the battery pack as described in claim 11, wherein the battery pack serves as the power supply for the terminal.